KONTROL ADAPTIF PADA MODEL PENYEBARAN KOLERA DENGAN ADANYA KETIDAKPASTIAN PARAMETER - Ayu, Regina Wahyudyah Sonata; Aulia, Hanna Hilyati (Universitas Islam Negeri Imam Bonjol Padang, 2021)
In this paper the number of humans infected with cholera was controlled under the uncertainty in cholera model parameters. The aim of this research is to design an adaptive control so that the number of infected humans decreases. To achieve this goal, an adaptive controller was proposed to a deterministic model for the transmission of cholera involving five state variables (susceptible humans, infected humans, quarantined humans, recovered humans, and bacterial concentration) and one input control variable, i.e, the proportion of quarantined humans. A control law was designed such that the number of infected humans was decreased tracking the given reference function. The tracking error convergence were analyzed by employing the Lyapunov theorem. The performance of the proposed controller was evaluated through numerical simulations. The results show that the adaptive controller designed to the model ensures the tracking error convergence such that the number of infected humans has declined.